Effect of malachite green toxicity on non target soil organisms. (February 2015) - Gopinathan, R.; Kanhere, J.; Banerjee, J.
Highlights: Malachite green (MG) toxicity was tested on beneficial soil bacteria, fungi, earthworms and on seed germination of crop plants. Genotoxicity, cytotoxicity and scanning electron microscopy assays concluded malachite green induced toxicity in soil microorganisms. Filter paper and artificial soil test on earthworms demonstrated a LC 50 of 2.6 mg/cm −2 and 1.45 mg/kg respectively with evident morphological alterations. Seed germination of Mung bean, Wheat and Mustard is unaffected in presence of MG upto 100 ppm. MG negatively effects growth, physiology of tested soil borne micro organisms and earthworms raising concerns about its environmental hazard. Abstract: Although malachite green (MG), is banned in Europe and US for its carcinogenic and teratogenic effect, the dye being cheap, is persistently used in various countries for fish farming, silk, dye, leather and textile industries. Current research, however, fails to elucidate adequate knowledge concerning the effects of MG in our ecosystem. In the present investigation, for the first time, an attempt has been made to study the effects of MG on soil biota by testing Bacillus subtilis, Azotobacter chroococcum, Saccharomyces cerevisiae, Penicillium roqueforti, Eisenia fetida and seeds of three crop plants of different families. Various tests were conducted for determining cytotoxicity, genotoxicity, acute toxicity, morphological and germination effect. Our data confirmed MG toxicity on fungi and bacteria (gram positive and gram negative organisms) showing elevated level of ROS. Genotoxicity caused in the microorganisms was detected by DNA polymorphism and fragmentation. Also, scanning electron microscopy data suggests that the inhibitory effect of MG to these beneficial microbes in the ecosystem might be due to pore formation in the cell and its eventual disruption. Filter paper and artificial soil test conducted on earthworms demonstrated a LC 50 of 2.6 mg cm −2 and 1.45 mg kg −1 respectively with severe morphological damage. However, seed germination of Mung bean, Wheat and Mustard was found to be unaffected in presence of MG up to 100 mg L −1 concentration. Thus, understanding MG toxicity in non target soil organisms and emphasis on its toxicological effects would potentially explicate its role as an environmental contaminant.